The impact of immediate initiation of antiretroviral therapy on patients' healthcare expenditures: a stepped-wedge randomized trial in Eswatini - Steinert, Janina; Khan, Shaukat; Mafara, Emma; Wong, Cebele; Mlambo, Khudzie; Hettema, Anita; Walsh, Fiona J.; Lejeune, Charlotte; Mazibuko, Sikhathele; Okello, Velephi; Ogbuoji, Osondu; De Neve, Jan-Walter; et al. (Aids and behavior, 2021)
Immediate initiation of antiretroviral therapy (ART) for all people living with HIV has important health benefits but implications for the economic aspects of patients' lives are still largely unknown. This stepped-wedge cluster-randomized controlled trial aimed to determine the causal impact of immediate ART initiation on patients’ healthcare expenditures in Eswatini. Fourteen healthcare facilities were randomly assigned to transition at one of seven time points from the standard of care (ART eligibility below a CD4 count threshold) to the immediate ART for all intervention (EAAA). 2261 patients living with HIV were interviewed over the study period to capture their past-year out-of-pocket healthcare expenditures. In mixed-effects regression models, we found a 49% decrease (RR 0.51, 95% CI 0.36, 0.72, p < 0.001) in past-year total healthcare expenditures in the EAAA group compared to the standard of care, and a 98% (RR 0.02, 95% CI 0.00, 0.02, p < 0.001) decrease in spending on private and traditional healthcare. Despite a higher frequency of HIV care visits for newly initiated ART patients, immediate ART initiation appears to have lowered patients’ healthcare expenditures because they sought less care from alternative healthcare providers. This study adds an important economic argument to the World Health Organization’s recommendation to abolish CD4-count-based eligibility thresholds for ART.
Gesehen am 21.04.2021